Words of life: scripture as the living and active word of God - Ward, Timothy (IVP Academic, 2009)
Introduction: God and the Bible -- God and Scripture : a biblical outline -- God's action and his words -- The Old Testament -- The New Testament -- God's person and his words 26 -- God's words and human words -- Christ's words, and God's action and person -- Christ's words and human words -- God's words and the Bible -- The Trinity and Scripture : a theological outline -- The Father and Scripture : the covenant book -- Redemption and Scripture -- Revelation and Scripture -- The Son and Scripture : the Words of the Word -- Jesus and the Bible as both Word of God -- Scripture and the incarnation -- The Holy Spirit and Scripture : the God-breathed Word -- The inspiration of Scripture -- The preservation of Scripture -- The illumination of Scripture -- The attributes of Scripture : a doctrinal outline -- The necessity of Scripture -- The sufficiency of Scripture -- The clarity of Scripture -- Preaching and a clear Bible -- Diverse interpretations and a clear Bible -- Defining the clarity of Scripture -- The authority of Scripture -- The nature of biblical authority-- Inerrancy and infallibility -- The Bible and Christian life : the doctrine of Scripture applied -- The meaning of sola scriptura -- Scripture and the Christian community -- Scripture and preaching -- The spirit and the Bible -- The spirit and the preacher -- The spirit and the people of God -- Scripture and the individual Christian -- Private Bible reading in relation to corporate -- Bible reading and preaching -- The aim of Bible reading